2012
DOI: 10.4103/0973-1482.98994
|View full text |Cite
|
Sign up to set email alerts
|

Primary amyloidosis with high grade transitional cell carcinoma of bladder: A rare case report

Abstract: Primary amyloidosis of bladder is a rare disease that closely resembles bladder cancer on clinical presentation with painless gross hematuria. Pathologically this is a totally benign non-neoplastic lesion and its association with urothelial carcinoma of the bladder is rare. We herein report a 64-year-old diabetic male who has been treated for primary amyloidosis of bladder for the last 26 years presented recently with high-grade solid urothelial cancer with osseous metaplasia and sarcomatoid change of bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 5 publications
0
15
0
2
Order By: Relevance
“…In some patients cystectomy is necessary owing to irritative symptoms or gross haematuria [4]. Instillation with dimethyl sulfoxide therapy has also been successful [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some patients cystectomy is necessary owing to irritative symptoms or gross haematuria [4]. Instillation with dimethyl sulfoxide therapy has also been successful [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare condition, with approximately 200 cases reported in the literature [4]. To the authors' knowledge, there have been only three prior cases with coexisting transitional cell carcinoma (TCC) and amyloidosis in the bladder [5]. This report presents three cases of amyloidosis in the bladder, of which two coexisted with TCC.…”
Section: Introductionmentioning
confidence: 91%
“…A series of 11 case reports matching our criteria were gathered (Table 1), available to be discussed [2,[4][5][6][7][8][9][10][11][12][13]. Our search was limited concerning the time period, beginning in 1991, as Eble and Young in that year published a review of the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that the majority of reported cases of primary urinary bladder amyloidosis manifest as solitary, localized polypoidal lesions 2, 3. However some studies have shown these amyloid lesions may become disseminated and progress even leading to upper urinary tract obstruction 4 . This warrants long-term follow-up, typically in the form of flexible cystoscopic surveillance in cases with primary bladder amyloidosis.…”
Section: Introductionmentioning
confidence: 99%